Interaction of African American Learners Online: An Adult Education Perspective. Issue 2 (2nd April 2016) - Kang, Haijun; Yang, Yang
ABSTRACT: This study examines how various life factors and personal attributes affect African American adult learners' use of the three types of learning interaction—learner–content, learner–instructor, and learner–learner. Multivariate multiple regression analyses were used. The aggregate effect of life factors on African American adult learners' use of the three types of learning interaction is strong whereas the aggregate effect of personal attributes shows minimal predictive power. This study confirms the importance of using adult learning theories and principles to understand the nature of adult learning online.